Oxford think! new syllabus Mathematics 2 (workbook) - Har, Dr Yeap Ban (Karachi : Oxford university press, 2024)
The "Think! New Syllabus Mathematics 2 Workbook (8th Edition)" is a companion workbook designed to help middle school students practice and reinforce the concepts introduced in the Think! New Syllabus Mathematics 2 textbook. The workbook is focused on providing additional exercises that strengthen students' mathematical skills and understanding.
Keywords: Math : Workbook; Oxford : 8th Edition